Chest pain with increased troponin level; not always a cardiology issue - Papadatos Stamatis S.; Karakatsanis Stamatis J.; Deligiannis George; Gatsa Eleni (Sciendo, 2019)
Thrombotic Thrombocytopenic Purpura (TTP) is a thrombotic microangiopathy syndrome resulting from decrease or absence of "a disintegrin and metalloproteinase with a thrombospondin type 1 motif member 13" (ADAMTS13). TTP has been characterized by the classical pentad of thrombocytopenia, hemolysis, fever, renal injury and neurological deficits, yet the patient may present with any atypical symptom related to microthrombi formation in the microcirculation. Here we present a rare case of a young patient with retrosternal chest pain and myocardial injury as the first manifestation of TTP.